2010
DOI: 10.1111/j.1750-3841.2010.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Effects of High‐Pressure Treatment on Salmonella enterica Serovar Typhimurium Inoculated into Peanut Butter and Peanut Products

Abstract: About 1.2 billion pounds of peanut butter are consumed annually in the United States. In 2008 to 2009, an outbreak involving Salmonella Typhimurium in peanut butter led to a recall of over 3900 products by over 200 companies. More than 700 people became sick, 100 were hospitalized, and 9 people died from this outbreak. This study examines the efficacy of high-pressure processing (HPP) to decrease S. Typhimurium American Type Culture Collection (ATCC) 53647 inoculated into peanut butter and model systems. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…These technologies need to be further examined for scale-up feasibility and efficacy. For example, a study examining high-pressure processing (HPP; 600 MPa for 5 min at 45 C) against inoculated Salmonella in peanut butter found only <2 log unit reductions (Grasso, Somerville, Balasubramaniam, & Lee, 2010). Since a 6.7 log unit reduction by HPP was achieved in a mixture of peanut flour and water, the fat content in oil could have provided protection for pathogens.…”
Section: Control Technologiesmentioning
confidence: 98%
“…These technologies need to be further examined for scale-up feasibility and efficacy. For example, a study examining high-pressure processing (HPP; 600 MPa for 5 min at 45 C) against inoculated Salmonella in peanut butter found only <2 log unit reductions (Grasso, Somerville, Balasubramaniam, & Lee, 2010). Since a 6.7 log unit reduction by HPP was achieved in a mixture of peanut flour and water, the fat content in oil could have provided protection for pathogens.…”
Section: Control Technologiesmentioning
confidence: 98%
“…In 2008 to 2009, an outbreak involving Salmonella Typhimurium in peanut butter led to a recall of over 3,900 products by over 200 companies. More than 700 people became sick, 100 were hospitalized, and 9 people died from this outbreak (Grasso et al 2010). Shachar and Yaron (2006) studied the heat tolerance of Salmonella enterica serovars Agona, Enteritidis, and Typhimurium in peanut butter and reported that the thermal treatments are inadequate to consistently destroy Salmonella in highly contaminated peanut butter and that the pasteurization process cannot be improved significantly by longer treatment or higher temperatures.…”
Section: Peanut Buttermentioning
confidence: 99%
“…Similar results were also reported by Ma et al (2010), thermal treatments of peanut butter at 90°C for less than 30 min were not sufficient to kill large populations (5 log CFU/g) of Salmonella in highly contaminated peanut butter. Grasso et al (2010) examined the efficacy of high-pressure processing (HPP) to decrease S. Typhimurium American Type Culture Collection (ATCC) 53647 inoculated into peanut butter and model systems and reported that because of the protective effect of oil HPP may not help the microbial safety of water-in-oil food emulsions including peanut butter. Hvizdzak et al (2010) studied the effectiveness of electron beam (E-beam) radiation (0 to 3.1 kGy) for the reduction of Salmonella serovars Tennessee (ATCC 10722) and Typhimurium (ATCC 14028) in creamy peanut butter.…”
Section: Peanut Buttermentioning
confidence: 99%
“…Peanut butter, which usually contains over 90% peanuts with optional added sweeteners, salt and stabilizers (Grasso et al, 2010), constitutes the largest segment of peanut consumption. This is due to the increase in the consumption of peanut butter from 1999 to 2008 while peanut candy and snack consumption has not (USDA, 2010).…”
Section: Introductionmentioning
confidence: 99%